2007
DOI: 10.1143/jjap.46.7212
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Si-Based Thin-Film Solar Cells Fabricated on Amorphous to Microcrystalline Silicon Transition Phase

Abstract: The temperature dependence of silicon (Si)-based thin-film single-junction solar cells, whose intrinsic absorbers were fabricated on the transition phase between hydrogenated amorphous silicon (a-Si:H) to hydrogenated microcrystalline silicon (mc-Si:H), was investigated. By varying the hydrogen dilution ratio, wide-band-gap protocrystalline silicon (pc-Si:H) and mc-Si:H absorber layers were obtained. Photo-current density-voltage (Photo-J-V) characteristics were measured under AM1.5 illumination at ambient tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
(35 reference statements)
4
17
0
Order By: Relevance
“…10(b) shows the results for the 3-kW p c-Si PV generators mounted with the fixed tilt angle of 10 and 35 . In general, the outdoor electricity-generation of the PV generators is affected by the module temperature, planeof-array irradiance [26], spectral distribution [26,27], temperature coefficient [28], transmittance of aged PV glasses [29] and aged EVA films [30], dust effect [31e33], and partial shading effect on PV modules [34,35]. The superstrate-type a-Si:H single-junction PV modules may be free from the effect of the aged EVA films, however it is also significantly impacted by the Staebler-Wronski effect [27,36].…”
Section: Resultsmentioning
confidence: 99%
“…10(b) shows the results for the 3-kW p c-Si PV generators mounted with the fixed tilt angle of 10 and 35 . In general, the outdoor electricity-generation of the PV generators is affected by the module temperature, planeof-array irradiance [26], spectral distribution [26,27], temperature coefficient [28], transmittance of aged PV glasses [29] and aged EVA films [30], dust effect [31e33], and partial shading effect on PV modules [34,35]. The superstrate-type a-Si:H single-junction PV modules may be free from the effect of the aged EVA films, however it is also significantly impacted by the Staebler-Wronski effect [27,36].…”
Section: Resultsmentioning
confidence: 99%
“…6. Regarding our previous study, the TC value for η of µc-Si:H single-junction solar cells was found in the range of -0.45 to -0.66%/ o C [9], whereas TC for η of pc-Si:H single-junction solar cells was about -0.20 to -0.30%/ o C [10][11]. We found that the temperature dependence of double-junction solar cells showed a similar behavior to single-junction solar cells.…”
Section: Temperature Dependence Of Pc-si:h/µc-si:h Double-junction Somentioning
confidence: 48%
“…In case of pc-SiO:H solar cells, the carbon dioxide concentration (CC=CO 2 /[CO 2 +SiH 4 ]) ratio was kept constant at 0.07 while SC was varied. More details for the fabrication of pc-Si:H and pc-SiO:H single-junction solar cells were explained in elsewhere [10,16]. Some deposition conditions in each layer are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations